Appraisal of heavy and trace metals in the sediments and fish ( Hemisynodontis membraneceous ) from Alaro stream in Ibadan, Nigeria (2014)
A study was carried out on the assessment of heavy and trace metals in the sediments and fish (Hemisynodontis membranaceous) from Alaro stream in Ibadan, Nigeria from July to December. Twenty-five fish were collected using cast and gill nets. Fish organs assessed were muscle, liver, bone, gut, gills and fins, while the sediments were collected from five sites that comprised of a control, three effluent receivers and a recovery site. The facility used for the assessment of the heavy and trace metals was the inductively couple plasma-mass spectrometer (ICP-MS) for accuracy of the results while quality assurance was ensured using bovine liver and San Joaquin standard reference materials. Heavy and trace metals assessed were Na, Mg, K, Ca, V, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo,Ag, Cd and Pb .Heavy and trace metal levels in the liver of both fishes were significantly higher than the other tissues (P>0.05). The fish muscle that is mainly and highly consumed was found to be relatively higher in the accumulation of the heavy and trace metals thereby making it unfit for consumption. The control site (site 1) and recovery site (site 5) were significantly lower in sediment heavy and trace metals while sites 2, 3 and 4 were higher due to industrial effluents discharged into them. Sediment heavy and trace metals from the effluent sites were found to exceed the limit guidelines given by the Federal Environmental Protection Agency. The study concludes that Alaro stream is polluted with its fisheries products